Harper's Round Table, February 25, 1896 - Various (Salt Lake City, UT : Project Gutenberg, 2017)
"Harper's Round Table, February 25, 1896" by Various is a collection of periodical literature written during the late 19th century. This publication brings together a variety of stories, articles, and illustrations aimed at a youthful audience, reflecting the societal values and interests of the time. Among its featured works is "Rick Dale," a story set on the Northwest Coast, which follows the life of Alaric Dale Todd, a boy grappling with the challenges of wealth, identity, and the desire for adventure. The opening of "Rick Dale" introduces Alaric, who feels burdened by his name and the sheltered life it represents. Described as a frail yet intellectually gifted young man from a wealthy family, Alaric has never engaged in typical boyish activities due to his overprotective upbringing. Following the death of his mother, he struggles with feelings of isolation and aims to break free from his confining lifestyle. His interactions with his lively cousin, Esther, catalyze a turning point for him, instilling in him hopes of adventure and the courage to challenge the limitations imposed upon him, thus setting the stage for his development throughout the story. (This is an automatically generated summary.)
Release date is 2017-04-02
Produced by Annie R. McGuire
Keywords: Children's periodicals